TCR-transgenic T cells and YB-1-based oncolytic virotherapy improve survival in a preclinical Ewing sarcoma xenograft mouse model - Schober, Sebastian J.; Thiede, Melanie; Gassmann, Hendrik; von Ofen, Anna Josefine; Knoch, Pia; Eck, Jennifer; Prexler, Carolin; Kordass-Wally, Corazon; Hauer, Julia; Burdach, Stefan; Holm, Per Sonne; Thiel, Uwe (Frontiers in Immunology, 2024)
Background: Ewing sarcoma (EwS) is an aggressive and highly metastatic bone and soft tissue tumor in pediatric patients and young adults. Cure rates are low when patients present with metastatic or relapsed disease. Therefore, innovative therapy approaches are urgently needed. Cellular- and oncolytic virus-based immunotherapies are on the rise for solid cancers. Methods: Here, we assess the combination of EwS tumor-associated antigen CHM1319-specific TCR-transgenic CD8+ T cells and the YB-1-driven (i.e. E1A13S-deleted) oncolytic adenovirus XVir-N-31 in vitro and in a xenograft mouse model for antitumor activity and immunostimulatory properties. Results: In vitro both approaches specifically kill EwS cell lines in a synergistic manner over controls. This effect was confirmed in vivo, with increased survival using the combination therapy. Further in vitro analyses of immunogenic cell death and antigen presentation confirmed immunostimulatory properties of virus-infected EwS tumor cells. As dendritic cell maturation was also increased by XVir-N-31, we observed superior proliferation of CHM1319-specific TCR-transgenic CD8+ T cells only in virus-tested conditions, emphasizing the superior immune-activating potential of XVir-N-31. Conclusion: Our data prove synergistic antitumor effects in vitro and superior tumor control in a preclinical xenograft setting. Combination strategies of EwS-redirected T cells and YB-1-driven virotherapy are a highly promising immunotherapeutic approach for EwS and warrant further evaluation in a clinical setting.